(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Strategic aspects of purchasing function have been considered in many construction companies as they influence the performance of the projects and hence the company performance in mostly contractors. Some studies have also been done to explore the impact of strategic function in domain purchasing. As on one of construction company in Indonesia, PT XYZ has been experiencing problem with their project schedule performance in the last three years and one of the affecting factors is unorganized purchasing of long lead items. Furthermore, the purchasing activities were performed in an ad-hoc way and not considering integration of purchasing activities from other projects. This study has a purpose to explore the influence of strategic purchasing relationship between the purchasing activities and the project schedule performance. The data was collected from 50 respondents using structured questionnaires. The data was analyzed using partial least square structural equation model with software SmartPLS 3.0. The result of this study shows a significant full mediation strategic purchasing to the relationship between purchasing process and project schedule performance